Participatory Vulnerability Assessments in support of Community Based Adaption - Rosimo, Magnolia M.; Vidallo, Rene R.; Dalusag, Joanna B.; Bernardo, Eisen Bernard; Monville-Oro, Emilita; Rosales, Belina O; Cabriole, Marie Aislinn; Gonsalves, Julian Francis (International Institute of Rural Reconstruction, 2021)
This publication is derived from a real life exercise in applying participatory vulnerability methods in 11 villages/barangays in the Municipality of Guinayangan , Quezon, Philippines. These villages were among those designated as climate smart villages, under the CCAFS global initiative to set up climate smart villages as platforms for climate-smart agriculture (CSA). The project in the Philippines was entitled “Generating an evidence base for upscaling local adaptation thorough Climate Smart Agriculture “(P56). This compilation includes tools and methods, facilitators guides and the actual outputs from the 9 villages.